Perioperative use of iloprost in cardiac surgery patients diagnosed with heparin‐induced thrombocytopenia‐reactive antibodies or with true HIT (HIT‐reactive antibodies plus thrombocytopenia): An 11‐year experience. Issue 7 (July 2015) - Palatianos, George; Michalis, Alkiviadis; Alivizatos, Petros; Lacoumenda, Stavroula; Geroulanos, Stefanos; Karabinis, Andreas; Iliopoulou, Eugenia; Soufla, Giannoula; Kanthou, Chryso; Khoury, Mazen; Sfyrakis, Petros; Stavridis, George; et al.
<x xml:space="preserve">Abstract</x> Thrombocytopenia and thromboembolism(s) may develop in heparin immune‐mediated thrombocytopenia (HIT) patients after reexposure to heparin. At the Onassis Cardiac Surgery Center, 530 out of 17, 000 patients requiring heart surgery over an 11‐year period underwent preoperative HIT assessment by ELISA and a three‐point heparin‐induced platelet aggregation assay (HIPAG). The screening identified 110 patients with HIT‐reactive antibodies, out of which 46 were also thrombocytopenic (true HIT). Cardiac surgery was performed in HIT‐positive patients under heparin anticoagulation and iloprost infusion. A control group of 118 HIT‐negative patients received heparin but no iloprost during surgery. For the first 20 patients, the dose of iloprost diminishing the HIPAG test to ≤5% was determined prior to surgery by in vitro titration using the patients' own plasma and donor platelets. In parallel, the iloprost "target dose" was also established for each patient intraoperatively, but before heparin administration. Iloprost was infused initially at 3 ng/kg/mL and further adjusted intraoperatively, until ex vivo aggregation reached ≤5%. As a close correlation was observed between the "target dose" identified before surgery and that established intraoperatively, the remaining 90 patients were administered iloprost starting at the presurgery identified "target dose." This process significantly reduced the number of intraoperative HIPAG reassessments needed to determine the iloprost target dose, and reduced surgical time, while maintaining similar primary clinical outcomes to controls. Therefore, infusion of iloprost throughout surgery, under continuous titration, allows cardiac surgery to be undertaken safely using heparin, while avoiding life‐threatening iloprost‐induced hypotension in patients diagnosed with HIT‐reactive antibodies or true HIT. Am. J. Hematol. 90:608–617, 2015. © 2015 Wiley Periodicals, Inc.